2022
DOI: 10.3390/toxins14020071
|View full text |Cite
|
Sign up to set email alerts
|

Khat, a Cultural Chewing Drug: A Toxicokinetic and Toxicodynamic Summary

Abstract: Khat (Catha edulis) is a recreational, chewed herbal drug that has been used as a psychostimulant for centuries in East Africa and the Arabian Peninsula, namely in Somalia, Ethiopia, and Yemen. However, the growing worldwide availability of khat has produced widespread concern. The plant comprises a large number of active substances, among which cathinone, cathine, and norephedrine are the main constituents, which can be included in the group of sympathomimetics of natural origin. In fact, these compounds are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 56 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…Khat chewing was also found to be an independent predictor of anemia in our study population. Because of its amphetamine-like stimulant effects [ 48 ], khat chewing has become an epidemic in Yemen, and a common practice among high school, college, and university students [ 40 , 49 ]. Previous studies have reported on the association between khat chewing and anemia, which could be explained by its potential impact on appetite [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khat chewing was also found to be an independent predictor of anemia in our study population. Because of its amphetamine-like stimulant effects [ 48 ], khat chewing has become an epidemic in Yemen, and a common practice among high school, college, and university students [ 40 , 49 ]. Previous studies have reported on the association between khat chewing and anemia, which could be explained by its potential impact on appetite [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, khat contains a substantial amount of tannins, which can reduce the bioavailability of non-heme iron from plant-based foods, which represent the basis of the population’s diet in Yemen [ 55 , 56 ]. The WHO reported that khat chewing may cause dependency [ 57 , 58 , 59 , 60 , 61 ], while predisposing chewers to an array of serious medical conditions [ 48 ]. Raising awareness about the adverse health impacts of khat chewing, and the provision of medical and nutritional management that targets khat chewers, are important points for the prevention of undernutrition and anemia among adolescents in Yemen.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, long-term Khat consumption poses a risk of developing severe complications including hepatitis, hepatic fibrosis, and cirrhosis in advanced stages. 25 Future prospective and more inclusive studies are recommended to investigate this issue, particularly in our country where the traditional use of these plants is widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent works even in our group reviewed both Khat and synthetic cathinones [ 157 , 187 ] are worth looking for further and more detailed information.…”
Section: Cathinonementioning
confidence: 99%